7‐Ketocholesterol‐induced lysosomal dysfunction exacerbates vascular smooth muscle cell calcification via oxidative stress. (30th September 2015) - Sudo, Ryo; Sato, Fumiaki; Azechi, Takuya; Wachi, Hiroshi
Abstract : Vascular calcification is known to reduce the elasticity of aorta. Several studies have suggested that autophagy–lysosomal pathway (ALP) in vascular smooth muscle cells (VSMCs) is associated with vascular calcification. A major component of oxidized low‐density lipoproteins, 7‐ketocholesterol (7‐KC), has been reported to promote inorganic phosphorus (Pi)‐induced vascular calcification and induce ALP. The aim of this study was to unravel the relationship between ALP and the progression of calcification by 7‐KC. Calcification of human VSMCs was induced by Pi stimulation in the presence or absence of 7‐KC. FACS analysis showed that 7‐KC‐induced apoptosis at a high concentration (30 μm ), but not at a low concentration (15 μm ). Interestingly, 7‐KC promoted calcification in VSMCs regardless of apoptosis. Immunoblotting and immunostaining showed that 7‐KC inhibits not only the fusion of autophagosomes and lysosomes but also causes a swell of lysosomes with the reduction of cathepsin B and D. Moreover, lysosomal protease inhibitors exacerbated the apoptosis‐independent calcification by 7‐KC although inhibition of autophagosome formation by Atg5 siRNA did not. Finally, the 7‐KC‐induced progression of calcification was alleviated by the treatment with antioxidant. Taken together, our data showed that 7‐KC promotes VSMC calcification through lysosomal‐dysfunction‐dependent oxidative stress. Abstract : In our in vitro study, we demonstrated that the lysosomal‐dysfunction‐dependent oxidative stress played a pivotal role in the progression of vascular smooth muscle cells calcification by a low concentration of 7‐ketocholesterol, and that even normal serum levels of 7‐ketocholesterol can be a risk factor for vascular calcification.